Nine key concepts for an education informed by evidence - Trinchero, Roberto (Formazione & insegnamento, 2017)
Educational activities are often governed by naive beliefs, not based on a solid empirical basis but deeply rooted among teachers, educators and trainers. Starting from a set of widespread beliefs, the article presents some key concepts emerging from meta-analysis in education and learning research. The idea is to provide a reference system for planning pathways and learning environments that can support effective training.